Tracing the Source of the Non-Native Philippine Population of the Greenhouse Frog Eleutherodactylus planirostris (Cope, 1862) through DNA Barcodes - Que, Gerard Clinton L.; Sy, Emerson Y.; Ong†, Perry S.; Fontanilla, Ian Kendrich C. (Science Diliman: A Journal of Pure and Applied Sciences, 2020)
Eleutherodactylus planirostris (Cope 1862), commonly called the Greenhouse Frog, is an insectivorous, direct-developing frog native to the Caribbean. It has been widely introduced outside of its native range and has been known to reach population densities of bout 12,500 frogs per hectare, posing a potential ecological threat in areas of its introduction, especially to local insect populations. Recently, the species has been detected on several islands throughout the Philippines. Samples for this study were obtained from two locations in Quezon City (Luzon Island) and one location in Bacolod City (Negros Island). DNA barcoding using three genes (Cytochrome b , 16S rDNA, and Cytochrome Oxidase subunit 1) was performed with the objective of identifying the source population of Philippine E. planirostris . Our results indicate that E. planirostris samples in the Philippines are identical genetically to populations in Hawai’i and Florida, USA and are closely related to an individual from Matanzas, Cuba. A haplotype network built using the Fitch algorithm also supports the Cuban origin of the Philippine samples. Moreover, the Philippine specimens have nearly identical sequences for all three genes, which may have implications on its success as an introduced species.
Keywords: DNA Barcoding, Eleutherodactylus planirostris, cytb, 16S, cox1, Cuba